If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + 9 = 2 * 3 Reorder the terms: 9 + y = 2 * 3 Multiply 2 * 3 9 + y = 6 Solving 9 + y = 6 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + y = 6 + -9 Combine like terms: 9 + -9 = 0 0 + y = 6 + -9 y = 6 + -9 Combine like terms: 6 + -9 = -3 y = -3 Simplifying y = -3
| http://www.wba.aplusanywhere.com/R85Content/mehttp://www.wba.aplusanywhere.com/R85Content/media/pictures/algebra1a/2_2_3i.gif?ts=1460992793374dia/pictures/algebra1a/2_2_3i.gif?ts=1460992793374 | | M+9m+7m+6= | | z/8-3=5 | | -3+9=2x | | http://www.wba.aplusanywhere.com/R85Content/media/pictures/algebra1a/2_2_3i.gif?ts=1460992793374 | | 149-y=259 | | 75-0.3(a/10)^2 | | 4x-1-s^2= | | 48/x=7.03 | | 45x=90x^2 | | 2(y+2)+3y=14 | | -5x+10x-77=-2 | | 75-0.3(a/10) | | 9/5c+32=0 | | 12=-4w+2(w-2) | | 1/4c-3=9 | | 2x(9x-8)=0 | | 2(1-7n)=-1b+47 | | 3x^3+1-7x=0 | | -15a+223=5a+123 | | 8+3(2a-5)-(3a+4)=3a-2(a+2) | | -19=7u+8(u+7) | | 21*4= | | log(7)(3x-5)=2+log(7)(x-6) | | 42x-18= | | 3/5y-8=-y | | 3/7(4-2)=2 | | 1.25x-3=30.5 | | 10x+5y=46 | | 4*(12/X)=7.03 | | 10x-9=8x+4 | | 1/4x^2-1/2x=6 |